2006
DOI: 10.1111/j.1525-1594.2007.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health‐related Quality of Life in Patients Treated With Hemodialysis in Serbia: Influence of Comorbidity, Age, and Income

Abstract: The importance of measuring health-related quality of life (HRQoL) in patients on maintenance hemodialysis (HD) is being increasingly recognized, but few studies, especially from the Balkan region, have addressed this issue. The aims of this study were (i) to evaluate HRQoL in an outpatient university-affiliated dialysis facility in South Serbia; (ii) to determine the effects of age, presence of comorbidity, primary kidney disease, dose of HD, and family income; and (iii) to make comparisons of the HRQoL in Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
4
12
0
1
Order By: Relevance
“…Yine yaş arttıkça yaşam kalitesinin düştü-ğü görülmüştür. Renal replasman tedavisi gören ve hemodiyalize giren kronik hastalarda yaş arttıkça, genel olarak yaşam kalitesinin düştüğü gösterilmiştir (15,16). Yaş ilerledikçe fonksiyonel yetersizliklerin yanı sıra, eşlik eden kronik hastalıklar nedeniyle yaşam doyumu azalmakta ve sonuç olarak yaşam kalitesinin düş-mesine neden olabilir (17).…”
Section: Discussionunclassified
“…Yine yaş arttıkça yaşam kalitesinin düştü-ğü görülmüştür. Renal replasman tedavisi gören ve hemodiyalize giren kronik hastalarda yaş arttıkça, genel olarak yaşam kalitesinin düştüğü gösterilmiştir (15,16). Yaş ilerledikçe fonksiyonel yetersizliklerin yanı sıra, eşlik eden kronik hastalıklar nedeniyle yaşam doyumu azalmakta ve sonuç olarak yaşam kalitesinin düş-mesine neden olabilir (17).…”
Section: Discussionunclassified
“…As such, assessment of HRQOL generally covers physical, social, and psychological domains [4]. Several studies proved that HD patients suffer poor HRQOL, despite continuing advancements in the treatment [3,4,[7][8][9][10][11][12][13][14]. Their HRQL is still much lower than general population [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…The association of age with HRQOL is quite complex and illustrates the complexity of the QOL concept [4] that age was strongly inversely associated with the physical domain scores. As age increases in the elderly, physical function of the body decreases [2,4,14,[18][19][20][21][22]. A recent Saudi showed that age was a negative predictor of HRQOL score [2].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic status has been reported as an important factor negatively associated with HRQOL in HD patients in Brazil (21) and Serbia (22). It is interesting to note that, in a study performed in the Netherlands (23), social factors were used by the doctors as contraindications to the adoption of PD by end-stage renal disease patients.…”
Section: Rossi Dos Santos Grincenkov Et Almentioning
confidence: 99%